ChemInform Abstract: Palladium‐Catalyzed α‐Arylation of 2‐Chloroacetates and 2‐Chloroacetamides. Issue 34 (1st August 2013) - Molander, Gary A.; Traister, Kaitlin M.; Barcellos, Thiago
Abstract The versatile scalable title reaction proceeds without using any strong bases or large excess of organometallic reagent.